2006
DOI: 10.1136/adc.2005.082388
|View full text |Cite
|
Sign up to set email alerts
|

Human metapneumovirus infections in hospitalised infants in Spain

Abstract: Background: Human metapneumovirus (hMPV) causes lower respiratory tract infections, particularly in young children and the elderly. Methods: A prospective study was conducted on the clinical characteristics of infants ,2 years of age admitted to hospital for respiratory infection and the characteristics of hMPV infections were compared with those of infections caused by respiratory syncytial virus (RSV). Influenza A, B and C viruses, RSV, parainfluenza viruses, and adenoviruses were simultaneously detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 37 publications
(17 reference statements)
6
35
1
5
Order By: Relevance
“…Although this article is highly confirmative to their previous study 2 and our matched pairs analysis, 3 it contains some interesting observations and conclusions we would like to comment on. As in our study, the authors have not found a significant difference in the clinical severity between HMPV and RSV-infections, although they did not used a matched pairs approach 3 but a random sample of 95 hospitalized infants-aged <2 and documented as RSV-infected.…”
Section: Hmpv Infections Are Frequently Accompanied By Co-infectionssupporting
confidence: 83%
“…Although this article is highly confirmative to their previous study 2 and our matched pairs analysis, 3 it contains some interesting observations and conclusions we would like to comment on. As in our study, the authors have not found a significant difference in the clinical severity between HMPV and RSV-infections, although they did not used a matched pairs approach 3 but a random sample of 95 hospitalized infants-aged <2 and documented as RSV-infected.…”
Section: Hmpv Infections Are Frequently Accompanied By Co-infectionssupporting
confidence: 83%
“…Moreover, in the present work, there were no deaths associated with hMPV infection. This was also reported by Garcia-Garcia et al (32) and Edwards et al (23). Nonetheless, data revealed that hMPV may induce serious disease, and fatal outcomes have been reported (33,34).…”
Section: Discussionsupporting
confidence: 86%
“…Since its first description in 2001 [36], the virus has been further identified in patients with RTIs from all continents [1,3,8,9,14,15,19,21,22,[27][28][29][30][31][32][33][34]41]. Seroprevalence studies in the Netherlands [36], Israel [44] and Japan [11] have shown that by the age of 5 to 10 years, seropositivity reaches virtually 100%.…”
Section: Introductionmentioning
confidence: 99%